Oxford junior dictionary - Dignen, Sheila (UK, Oxford university press, 2007)
g over 6000 entries in alphabetical order, this dictionary contains easy-to-read numbered meanings, and word classes. It features example sentences by children's authors, such as Dick King-Smith, Jacqueline Wilson and Roald Dahl. It includes information for spelling success, punctuation, simple grammar, prefixes and suffixes, and more.
Keywords: Oxford english language dictionaries